Browning’s Poetics of Necropolitical Power Dynamics - Sharma, Pradip (Bon Voyage, 2024)
This article explores the life-scaring power dynamics in Browning’s poetry regarding the social praxis of gender as staged by Robert Browning’s “Porphyria’s Lover” and “My Last Duchess.” To this end, it peruses these poems to show the poetic necropolitics; politics of death. Delving into the poems, the male chauvinist narrators hold the bodies of their female counterparts before annihilating them. Taking stock of necropolitical power wielded by the sovereign narrators, this paper aims to parse the deadening lives of the perpetrated Duchess and Porphyria. For this purpose, it deploys Achille Mbembe’s understanding of necropolitics as a critical insight that he imbibes from Michel Foucault’s biopolitical racism (that holds the authority to deploy alterity and expose life to death). Meanwhile, the study does not only expand the necropolitical literary explication of Browning’s poems, nonetheless, it attempts to reorient the readers to reexamine the alibi of the killers in the poems. Enthused by Mbembe’s acumen that revisits how power makes its subjects docile through political decisionism: “who must live and who must die,” this paper debates the sexist discourse of the killer-narrators and the living-dead ladies before their killing. Largely, it wonders to know how the subjects turn out to be the living dead or the object of male sadism. To elucidate this life-scaring politics; necropolitics, this paper also probes the presence (hegemonic existence) of sexist males that renders the female absent (non-existence) before they are immolated in the poems. It concludes that sexist patriarchy replicating the sovereign power constitutes the precarious life of the females via making them abject and invisible through ‘corpsing-policy’ which becomes a pertinent issue to rear humanism in Humanity Studies.